2012
DOI: 10.4049/jimmunol.1102341
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Superoxide Dismutase Inhibits Innate Immune Responses and Clearance of an Intracellular Bacterial Infection

Abstract: Reactive oxygen and nitrogen species (ROS/RNS) play important roles during immune responses to bacterial pathogens. Extracellular superoxide dismutase (ecSOD) regulates extracellular concentrations of ROS/RNS and contributes to tissue protection during inflammatory insults. The participation of ecSOD in immune responses seems therefore intuitive, yet is poorly understood. In the present study, we utilized mice with varying levels of ecSOD activity to investigate the involvement of this enzyme in immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 46 publications
(58 reference statements)
2
40
2
1
Order By: Relevance
“…A similar association has been demonstrated for the attenuated BCG strain and other mutants of virulent M. tuberculosis; failure to control intramacrophage ROS production leads to an increased production of pro-inflammatory cytokines (62)(63)(64)(65)(66). Conversely, restriction of host ROS via overexpression of host superoxide dismutase results in the suppression of pro-inflammatory cytokines and impaired clearance of Listeria monocytogenes (67). These studies indicate a conserved theme of ROS-dependent cell signaling in the generation of innate immune responses and provide conceptual evidence that bacterial antioxidant enzymes prevent this response by inhibiting redox-sensitive signaling.…”
Section: Discussionsupporting
confidence: 60%
“…A similar association has been demonstrated for the attenuated BCG strain and other mutants of virulent M. tuberculosis; failure to control intramacrophage ROS production leads to an increased production of pro-inflammatory cytokines (62)(63)(64)(65)(66). Conversely, restriction of host ROS via overexpression of host superoxide dismutase results in the suppression of pro-inflammatory cytokines and impaired clearance of Listeria monocytogenes (67). These studies indicate a conserved theme of ROS-dependent cell signaling in the generation of innate immune responses and provide conceptual evidence that bacterial antioxidant enzymes prevent this response by inhibiting redox-sensitive signaling.…”
Section: Discussionsupporting
confidence: 60%
“…As studies impressively demonstrated: superoxide is able to kill bacteria directly, especially when the virulence of the pathogen is dramatically attenuated (i.e. by superoxide dismutase deficiency) [46] [47]. Here in this study, the inhibition of specific glutamine-dependent pathways were one important constituent in the significant turnaround of the pyruvate-induced alterations in the immune parameters examined.…”
Section: Pyruvate Induced Effects: Is There An Impact By Adding a Glumentioning
confidence: 57%
“…We have previously shown that ecSOD enhances the recruitment of neutrophils to the liver in mice prior to and during L. monocytogenes infection (24). However, the mechanism by which ecSOD enhances neutrophil recruitment is not understood.…”
Section: Resultsmentioning
confidence: 99%
“…It was also demonstrated that ecSOD activity enhances neutrophil recruitment to the liver both prior to and during L. monocytogenes infection (24). This observation is counterintuitive, as ecSOD activity increases the susceptibility of mice to L. monocytogenes infection and neutrophils are known to protect against L. monocytogenes infection (25,26).…”
mentioning
confidence: 99%